Effect of nutrients and aeration on O2 evolution and photosynthetic pigments of Anabaena torulosa during akinete differentiation - Sarma, T A; Ahuja, G; Khattar, J I (Folia microbiologica, 2000)
The addition of a nitrogen (nitrate) and carbon sources (acetate, citrate and fructose) and phosphate deficiency (nitrate medium deficient in phosphate) under unaerated conditions induced akinete differentiation in Anabaena torulosa. Aerated cultures of this organism in these nutrients did not differentiate akinetes. Oxygen evolution by aerated cultures was higher when compared to unaerated cultures, which concurred with high chlorophyll content of aerated cultures. Nitrate nitrogen supported high phycocyanin content in unaerated cultures; phycocyanin and allophycocyanin contents were low under aerated conditions. The contents of phycocyanin, allophycocyanin, phycoerythrin and carotenoids gradually decreased at the mature akinete phase. Under aerated conditions, chlorophyll content rose and the content of all the pigments increased with the growth rate of the organism.
Keywords: vzduch; biologické pigmenty; Culture Media; kyslík; Anabaena; Oxygen; Photosynthesis; Air; fotosyntéza; Pigments, Biological; kultivační média